Bibliometric Trends in Research on Islam and Morality: Contextualizing Findings Within Qur’anic Thought - Al Faiz, Maftukh Khanan; Hasan, Abdul Kholiq; Azani, Mohammad Zakki; AN, Andri Nirwana (Universitas Muhammadiyah Surakarta, 2025)
This study addresses the underexplored global patterns in research on Islam and morality, which has been fragmented across various academic disciplines. The central problem lies in the absence of a comprehensive bibliometric analysis of the existing literature, leaving gaps in understanding the volume, thematic distribution, and geographical trends in the field. The objective of this research is to systematically map the academic output on Islam and morality by employing a bibliometric approach, focusing on the publications indexed in Scopus between 2015 and 2025. The methodology involves three stages: a literature review, a database search for relevant articles, and an in-depth analysis of publication trends, authorship, and thematic connections using tools like RStudio and VOSviewer. The findings indicate a substantial increase in research output from 2015 to 2024, with a notable peak in 2024, signaling a growing interest in the subject. Key thematic areas that emerged from the network analysis include morality, Islamic law, ethics, and gender, demonstrating the interdisciplinary nature of the field. The study also highlights a dominance of certain countries like Indonesia, the United States, and Turkey in contributing to the literature. The results suggest that Islam and morality are gaining importance not only in religious studies but also in bioethics, social sciences, and gender studies. The implications of this research stress the need for further exploration of underrepresented topics, such as sustainability and bureaucracy, and call for increased global collaboration to bridge knowledge gaps.